Critical Paradigm for the Implementation of Character Education in Schools: A Study of the Sociology of Education - Lestari, Febrianti T.; Haryanto, Sigit; Fuadi, Djalal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study critically examines the implementation of character education in schools through the perspective of educational sociology with a critical perspective. Using a qualitative research design with a literature study approach, this study analyzes the mechanisms of symbolic violence, the reproduction of social inequality, and power relations in the practice of character education. The results of the study revealed that the implementation of character education operates as an arena of meaning contestation where the values of the dominant group are hegemonized through curriculum and school practices. The mechanism of symbolic violence works through habituation that reproduces the habitus of the dominant class, while the power relations between teachers, students, and institutions shape conformist subjectivity through disciplinary and normalization technologies. Structural challenges such as limited resources, lack of teacher training, and low parental participation indicate that the problem of character education is political-paradigmatic. This research offers an alternative perspective that emphasizes an emancipatory approach through critical awareness, reflective pedagogy, and a commitment to social justice to transform character education from an instrument of social reproduction into a medium of liberation.